Approaches to formation of intellectual culture of the future teacher of an initial link in the course of vocational training - Тамбовська, Х. (Educational Dimension, 2012)
Tambovska H. Approaches to formation of intellectual culture of the future teacher of an initial link in the course of vocational training. In article, on the basis of the analysis of approaches of structure and ways of formation of intellectual culture of the person conditions which assist efficiency of the given process are considered; directions which are expedient for realising during vocational training of the future teacher of an initial link of formation, in particular formations of receptions of intellectual activity are shown.